Biochemical alterations induced in Hediste diversicolor under seawater acidification conditions. (June 2016) - Freitas, Rosa; Pires, Adília; Moreira, Anthony; Wrona, Frederick J.; Figueira, Etelvina; Soares, Amadeu M.V.M.
Abstract: Seawater pH is among the environmental factors controlling the performance of marine organisms, especially in calcifying marine invertebrates. However, changes in non-calcifying organisms (including polychaetes) may also occur due to pH decrease. Polychaetes are often the most abundant group of organisms in estuarine systems, representing an important ecological and economic resource. Thus, the present study aimed to evaluate the impacts of seawater acidification in the polychaete Hediste diversicolor, a species commonly used as bioindicator. For this, organisms were exposed to different pH levels (7.9, 7.6 and 7.3) during 28 days and several biochemical markers were measured. The results obtained demonstrated that pH decrease negatively affected osmotic regulation and polychaetes metabolism, with individuals under low pH (7.6 and 7.3) presenting higher carbonic anhydrase activity, lower energy reserves (protein and glycogen content) and higher metabolic rate (measured as Electron transport system activity). The increase on CA activity was associated to organisms osmoregulation capacity while the increase on ETS and decrease on energy reserves was associated to the polychaetes capacity to develop defense mechanisms (e.g. antioxidant defenses). In fact, despite having observed higher lipid peroxidation at pH 7.6, in polychaetes at the lowest tested pH (7.3) LPO levels were similar to values recorded in individuals under control pH (7.9). Such findings may result from higher antioxidant enzyme activity at the lowest tested pH, which prevented organisms from higher oxidative stress levels. Overall, our study demonstrated how polychaetes may respond to near-future ocean acidification conditions, exhibiting the capacity to develop biochemical strategies which will prevent organisms from lethal injuries. Such defense strategies will contribute for polychaetes populations maintenance and survival under predicted seawater acidification scenarios. Graphical abstract: Highlights: Hediste diversicolor counteract seawater acidification increasing their antioxidant capacity. With seawater acidification worms increased CA activity to maintain cellular homeostasis. pH decrease increased worms metabolic activity and the expenditure of energy reserves. Worms burrowing nature may contribute to the balance between survivors and non survivors.